THE CONSTRUCTION OF SOCIAL VALUES IN THE ORAL LITERATURE TRADITION “OLO” LANGGUDU MBOJO-BIMA - Siti Rahmatillah; Ma’rifatul Munjiah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2022)
This research aims to explain the meaning and social values contained in Olo's oral literary traditional. This research is a type of qualitative descriptive research, and includes field research. The data collection uses closed interview techniques.The validity of the data using resource triangulation, data analysis using the techniques of data collection, selection and reduction, presentation, analysis, data crosscheck and drawing conclusions. The results of this research are that Olo is an oral literature sing using bamboo gongs and flutes as accompanying traditional musical instruments. The social values in it contain the social values of love, mutual cooperation and solidarity in the social life. The social value of love is in the form of feelings of mutual love between a man and woman in the bonds of marriage, and the value of mutual cooperation where there is unity in working together to achieve common goals in the implementation of Olo literary tradition. The social value of solidarity in social life is the presence of fraternity, brotherhood and social relations in the life of society.